Enhancing Multimodal Learning Through Traditional Sporting Games: Marro360° - Lavega-Burgués, Pere; Luchoro-Parrilla, Rafael A.; Serna, Jorge; Salas-Santandreu, Cristòfol; Aires-Araujo, Pablo; Rodríguez-Arregi, Rosa; Muñoz-Arroyave, Verónica; Ensenyat, Assumpta; Damian-Silva, Sabrine; Machado, Leonardo; Prat, Queralt; Sáez de Ocáriz, Unai; et al. (Frontiers in Psychology, 2020)
Different international organizations and initiatives highlight the contribution of the traditional sporting game (TSG) to favor the diversity of knowledge, values and attitudes necessary for today's society. TSG such as Marro trigger multimodal learning contexts (driving behaviours, interpersonal and organic relationships), with great interest in the educational and sports initiation field. The purpose of two studies presented in this manuscript was to examine the 360º multimodal strategic intervention (decisional, relational and organic) of two teams faced in a Marro game. For this study, a quasi-experimental design was used composed by a single test applied to two non-equivalent teams. Mixed methods were used with an observational methodology in quadrant III: nomothetic, punctual and multidimensional. 14 university students participated (M = 20.49, SD = 2.18). Three internal logic variables were studied: outcome, role and subrole; and three variables referred to the dimensions of motor behaviour: relationship, risk in the decision and physical effort. A mixed ad hoc registration system was designed, with acceptable margins of data quality. For study 1, crosstabulations and classification trees were applied, while for study 2 strategic T-patterns were identified. The relevance of the scoreboard and the realization of the role (p <.001) for the study of multimodal strategic chains in the Marro game were confirmed. The detection of regularities in specific interaction (Hunters against Hares) by Theme (p <.005), allowed to interpret the process of strategic behaviours of both teams during the game. Knowing the strategic chains of playful coexistence among equals through a multimodal range of variables and approaches, has revealed an unusual dynamic picture. The study provides scientific evidence for the physical education teacher on the dynamics of the game of Marro. The pedagogical application of these contributions must be made according to curricular interests.